Expert Answers
justaguide eNotes educator| Certified Educator

To solve for a from the expression `3b = (9/13)(2a-6)` express a in terms of b.

`3b = (9/13)(2a-6)`

=> `2a - 6 = (3b)*(13/9)`

=> `2a - 6 = (13b)/3`

=> `2a = (13b)/3 + 6`

=> `a = (13b)/6 + 3`

The value of a in terms of the other variables is `a = (13b)/6 + 3`

rakesh05 eNotes educator| Certified Educator

`3b=(9/13)(2a-6)=>` `(2a-6)=(13.3/9)b`

                               `=>`     `2a=(13/3)b+6`

                              `=>`      `a=(13/6)b+3` .

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question